The role of works councils for severance payments - Grund, Christian; Martin, Johannes (Bonn, 2017)
"Using representative German employee data, we analyse the role of works councils for the incidence of severance payments subsequent to dismissals. While there is a positive relation with severance payments after those dismissals which stem from plant closings, the incidence of a works council is negatively associated with severance pay subsequent to individual layoffs. In both cases, we find a negative moderating effect of individuals' higher reemployment chances. We also explore gender differences and differences between the types of previously held jobs."